Markers of neutrophil activation and extracellular traps formation are predictive of appendicitis in mice and humans: a pilot study - Michael Boettcher; Melina Esser; Julian Trah; Stefan Klohs; Nariman Mokhaberi; Julia Wenskus; Madgalena Trochimiuk; Birgit Appl; Konrad Reinshagen; Laia Pagerols Raluy; Michaela Klinke (Scientific Reports, 2020)
Abstract Appendicitis is one of the most frequent emergencies in pediatric surgery, yet current biomarkers for diagnosis are unspecific and have low predictive values. As neutrophils and extracellular traps (ETs) are an essential component of the immune defense against bacterial infections, and appendicitis is considered an inflammation reaction of the appendix, we hypothesized that neutrophil activation and NET formation play an essential role in appendicitis development and maintenance. Therefore, this pilot study aimed to establish a murine model of appendicitis and to evaluate ETs markers to diagnose appendicitis in mice and humans. The study used 20 (12 appendicitis- and 8 controls) 6-week old mice which underwent advanced appendicitis induction using a modified caecal ligation puncture procedure. During the study, cell-free DNA, neutrophil elastase (NE), myeloperoxidase (MPO), and citrullinated Histone H3 (H3cit) were assessed. Additionally, samples of 5 children with histologically confirmed appendicitis and 5 matched controls with catarrhal appendicitis, were examined for the same biomarkers. Moreover, NE, MPO, and H3cit were assessed histologically via immunofluorescence in mice and humans. All mice in the appendicitis group developed an advanced form of appendicitis with focal peritonitis. In mice and humans with appendicitis, markers of neutrophil activation and ETs formation (especially cfDNA, NE and H3cit) were significantly elevated in blood and tissue compared to controls. Ultimately, biomarkers correlated extremely well with tissue expression and thus disease severity. It appears that neutrophil activation and possibly NETs contribute to appendicitis development and biomarkers of neutrophil activation and ET formation reflect disease severity and thus could be used as biomarkers for appendicitis. However, large prospective clinical studies are needed to confirm our findings.